El Niño Costero and occupation of the territory, Rimac river basin. Case: Chosica - Comeca Chuquipul, Miguel Ángel (2019)
In the summer of 2017 the north and central coast of Peru, endured rains as they had not been registered for many years, the departments of the north and center of the country were the most affected. In Lima, 80% of the identified streams were activated, causing mudslides and floods that affected the towns of Chosica, Huachipa, Carapongo, Cajamarquilla, Santa Eulalia, Campoy, among others, all located in the Rímac river basin. The occurrence of this phenomenon has been considered atypical by its magnitude and its improvised occurrence, for which the Multisectorial Committee in charge of the study of this phenomenon (ENFEN) called it «El Niño Costero». This natural phenomenon generated disasters such as the destruction of homes, land roads, bridges, schools and other infrastructure, especially in towns located in vulnerable areas. In this context, this research aims to explain the characteristics and impacts of this phenomenon and how it relates to the occupation of the territory by the population in risk areas, such as the bed and flooded terraces of the streams and the Rímac river, in the Chosica town located in its middle basin.